Comparative study of the ultrastructure and secretory dynamic of hypopharyngeal glands in queens, workers and males of Scaptotrigona postica latreille (Hymenoptera, Apinae, Meliponini) - Da Costa, Rosiléia Ana Cássia [UNESP]; Da Cruz-Landim, Carminda [UNESP] (My University, 2000)
The secretory cycle of hypopharyngeal glands (HPGs) in Scaptotrigona postica resembles that of Apis mellifera: in newly emerged workers the HPGs are in prefunctional state, their maximum development happens in the nurse workers and in forager workers they show signs of reabsorption. In S. postica these glands are also present in queens and males where they are more developed in newly emerged individuals. The ultrastructural features of the HPG secretory cycle in workers or S. postica and A. mellifera are alike: granular endoplasmic reticulum well developed, large secretion masses around the intracellular canaliculus in nurse workers and extensive degenerative structures in forager workers. Then it is suggested that the HPG secrete similar substances in both species. A second secretory cycle seems to occur in early foragers, may be with production of enzymes. The role of the HPGs in queens and males remains unknown but one possibility is enzyme production.
Keywords: Apidae; Function; Hypopharyngeal glands; Secretory cycle; Ultrastructure